Time Course of Changes during Continuous High-Volume Hemodiafiltration - N. V. Purlo; A. A. Levina; Yu. I. Mamukova; L. S. Biryukova (Общая реаниматология, 2008)
Objective: to evaluate changes in the levels of cytokines, ferritin, and endothelin in the peripheral blood and filtrates of patients with multiple organ dysfunctions during continuous high-volume hemodiafiltration (CHVHDF). Subjects and methods: Twenty-eight patients aged 32 to 69 years with the severity of disease of 31 to 36 APACHE II scores were examined. Results. Prior to CHVHDF, the patients were found to have elevated plasma proinflammatory cytokines. During CHVHDF, the bulk of cytokines were eliminated, the levels of some cytokines were higher in the filtrate than in the plasma, presumably, due to the dissociation of inflammatory mediators passing through the extracorporeal circuit. Conclusion. In survivors, the levels of TNF-a, IL-2, IL-6, and IL-10 were much higher, but those of IL-13 and ferritin were lower than those in deceased patients. By the end of treatment, there was a trend for cytokines to become normal in the survivors. The possibilities of using the level of some cytokines as predictors for the evaluation of patients’ condition will be determined after further studies. Key words: cytokines, continuous high-volume hemodiafiltration, multiple organ dysfunctions.